Criteria indicators characterizing picking maturity of apple fruits tree of the NCFCSHVW selection - T. G. Prichko; N. V. Droficheva; T. L. Smelik; M. G. Germanova (Новые технологии)
Harvesting picking maturity fruits is one of the ways to maximize the preservation of fruit quality during storage, since the use of modern highly effective technologies can be reduced to zero if the apples are harvested too soon or later. To assess the maturity of fruits it is necessary to use objective criteria characterizing the organoleptic, commodity and chemical indicators of fruit quality. To establish the optimal harvesting time, generalized criteria for the quality indicators of fruits in a varietal section are necessary, such as the hardness of the pulp, the starch content, soluble dry substances, sugars, acids. Therefore, the study of these criteria indicators, the degree of their variation will make it possible to establish optimal harvesting dates for fruits directly for the zone of the southern Russia, taking into account varietal characteristics. Apple fruits grown in horticultural farms of the Krasnodar Territory have been chosen as research objects to determine the criteria for characterizing the onset of fruit picking maturity. The article presents the results on the content of acids, starch, sugars, hardness of the pulp of apple fruit of NCFCSHVW selection, allowing to establish criteria for apples depending on varietal characteristics and weather conditions of the season, characterizing the optimal timing of fruit harvest.